A thousand sisters : my journey into the worst place on earth to be a woman - Shannon, Lisa, 1975- (Seal Press : Distributed by Publishers Group West, 2010)
The founder of the organization Run for Congo Women describes her visit to Congo and recounts the extreme hardships and tragic events in the lives of the women she meets there.